The Legal System Of The Floating Insurance Policy In Maritime Low (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The research dealt with the study of the legal system of the floating insurance policy ,This is by talking about the nature of the floating insurance policy, By explaining its definition in both law and jurisprudence, And then a statement of the legal nature of this document, whether it is a final insurance contract, apromise of the contract dependent on a condition, Determining the legal provisions applicable to this document that are dealt with in the field of maritime transport, The study concluded with a conclusion in which the main findings and recommendations of the research were stated.